High-dose rabeprazole-amoxicillin dual therapy and rabeprazole triple therapy with amoxicillin and levofloxacin for 2 weeks as first and second line rescue therapies for Helicobacter pylori treatment failures - Goh, Khean Lee; Manikam, J.; Qua, C.S. (Wiley, 2012)
BACKGROUND: H. pylori eradication failures are difficult to treat and rescue therapies often consist of complex treatment regimens. AIM: To determine an effective and practical rescue therapeutic strategy for H. pylori treatment failures using two consecutive regimens: first rescue therapy - rabeprazole 20 mg t.d.s. and amoxicillin 1 g t.d.s. for 2 weeks and for failures a further second rescue therapy - rabeprazole 20 mg b.d., levofloxacin 500 mg b.d., amoxicillin 1 g b.d. for a further 2 weeks. METHODS: Consecutive patients who failed the proton pump inhibitor (PPI) 1-week triple therapy were recruited for the study. H. pylori status was determined by a C(13) urea breath test. RESULTS: One hundred and forty-nine patients received the first rescue therapy. Seven were not compliant to medication/defaulted follow-up. Eradication success- first rescue therapy: per protocol (PP) analysis-107/142 (75.4%) (95% CI (68.3-82.4%) and intention to treat (ITT) analysis-107/149 (71.8%) 95% CI (64.6-79.0%). Thirty-one of 35 patients who failed the first rescue therapy received the second rescue therapy. All were compliant with medications. Eradication success- PP and ITT was 28/31 (90.3%) 95% CI (74.2-98.0%). The cumulative eradication rate using both rescue therapies: PP analysis- 135/138 (97.8%) 95% CI: (93.8-99.6%), ITT analysis- 135/149 (90.6%) 95% CI: (84.7-94.8%). CONCLUSIONS: A 2-week high dose PPI-amoxicillin dual therapy followed by a PPI-amoxicillin-levofloxacin triple therapy were highly successful in achieving eradication in H. pylori treatment failures.